Exhaust Fan Control Design As Air Cleaner Based On Microcontroller: Exhaust Fan Control Design As Air Cleaner Based On Microcontroller - Frinto Tambunan; Bambang T.J. Hutagalung; Nurhayati Nurhayati (Jurnal Mantik, 2020)
The use of Exhaust fan is a device that we often encounter in our daily lives. And in its use is still controlled by humans themselves and classified as manual, so manual use is very inconvenient to exhaust fan users, so that if it is controlled systematically using fuzzy logic, where the logic to be implanted is, to accelerate the exhaust fan rotation rate if a value is obtained that will refer at the high level of impurities detected by sensors that have been setup and determined in such a way, so that exhaust fan can work in accordance with what is instructed by the logic that is embedded in the microcontroller system.